UC-MSCs Secretome Induces Proliferation of CD4+ T Cells, CD8+ T Cells, NK Cells, and Increases sPD-1 Levels in Severe COVID-19’s Whole Blood - Winna Soleha; Heri Wibowo; Murdani Abdullah; Saraswati Pradipta; Lucky Novita Syari; Isabella Kurnia Liem; Arleni Bustami; Anna Rozaliyan (MCBS (Molecular and Cellular Biomedical Sciences))
Background: Clinical features of severe coronavirus disease 2019 (COVID-19) predominantly include respiratory symptoms and exacerbated multi-organ complications, especially in patients with comorbidities. Cellular immunity, including lymphocytes, is a critical factor in combating SARS-CoV-2 infection. However, immune dysregulation occurs in severe COVID-19 patients, characterized by cytokine storm and lymphopenia. The effectiveness of mesenchymal stem cell (MSC) therapies for COVID-19 is being assessed. The secretome released by MSC functions similarly to the cells themselves as an immunomodulator, offering potential advantages in terms of safety and cost-effectiveness. This study was conducted to assess the effect of umbilical cord MSC-derived (UC-MSC) secretome treatment on lymphocyte count and soluble programmed cell death-1 (sPD-1) levels in severe COVID-19 patient's whole blood. Materials and methods: Twelve whole blood samples from healthy individuals and severe COVID-19 patients were analyzed for lymphocyte count and functional activation using flow cytometry, along with sPD-1 level measurement in pre-treatment and post-secretome conditions. Results: The lymphocyte count in severe COVID-19 patients was significantly decreased, particularly for T cells and NK cells, indicating lymphopenia. Following secretome treatment, CD4+ T cell counts significantly increased compared to pre-treatment, although this change was not significant in the negative control group. Additionally, there was a minimal reduction in B cell count and an increase in sPD-1 levels. Elevated sPD-1 may alleviate T cell exhaustion by interfering with PD-1 binding to programmed death-ligand 1 (PD-L1). Conclusion: Administration of UC-MSC secretome to the whole blood of severe COVID-19 patients suggested immune improvement, with significant increases in CD4+ T cell counts, enhanced B cell survival, and elevated sPD-1 levels. Keywords: COVID-19, cellular immunity, lymphocytes, secretome, MSC